Wedding in the History and Culture of the Tatars - Gabdrakhmanova, Fanuza Haydarovna; Zamaletdinov, Radif Rifkatovich; Zamaletdinova, Gulnara Fandasovna (Journal of History Culture and Art Research, 2017)
The historical period and the associated cultural structure experienced by the nation in the past leave its more or less discernible imprint in the national mentality, which is, in fact, a series of successively overlapping cultural and historical layers. An integral part of the mentality is a set of values in general and each of its elements separately. To determine the semantic meaning contained in any of the values of the concepts of the era, it is necessary to consider not only the circumstance of this particular epoch, but also the historically preceding evolution of this value in the culture of the people. Proceeding from the above, in this article we have described the history of tuy (the wedding) and related social, legal, economic, religious, magical rites, its role, functions in the social life of the Tatar people. In the Tatar linguistic culture, the wedding expresses not only the universal idea of the transition of people marrying to another age and social status, but also is part of the family-household ritual that fixes the transitional stages of the person's life cycle: birth, marriage, death – gumernen uch tuye (three weddings of life). Many ritual acts performed at the time of marriage have deep historical roots, are repeated from time to time, change their content and meaning, but, nevertheless, despite the loss of their integrity, the tendency to wither away, the simplification of some ritual forms, traditional household rituals, being the most conservative sphere, connected with the field of traditional outlook and psychology, have preserved specific ethnic features.